BFEDroid: A Feature Selection Technique to Detect Malware in Android Apps Using Machine Learning - Chimeleze C.; Jamil N.; Ismail R.; Lam K.-Y.; Teh J.S.; Samual J.; Akachukwu Okeke C. (Hindawi Limited, 2023)
Android (operating system); Android malware; Classification (of information); Feature Selection; Learning systems; Mobile security; Android apps; Classification models; Feature weight; Features selection; Machine learning algorithms; Machine-learning; Malware detection; Malwares; Memory usage; Selection techniques; Learning algorithms